Potent inhibitors of equine steroid isomerase EcaGST A3-3. - Helena Lindström; Aslam M A Mazari; Yaman Musdal; Bengt Mannervik (PLoS ONE, 2019)
Equine glutathione transferase A3-3 (EcaGST A3-3) belongs to the superfamily of detoxication enzymes found in all higher organisms. However, it is also the most efficient steroid double-bond isomerase known in mammals. Equus ferus caballus shares the steroidogenic pathway with Homo sapiens, which makes the horse a suitable animal model for investigations of human steroidogenesis. Inhibition of the enzyme has potential for treatment of steroid-hormone-dependent disorders. Screening of a library of FDA-approved drugs identified 16 out of 1040 compounds, which at 10 μM concentration afforded at least 50% inhibition of EcaGST A3-3. The most potent inhibitors, anthralin, sennoside A, tannic acid, and ethacrynic acid, were characterized by IC50 values in the submicromolar range when assayed with the natural substrate Δ5-androstene-3,17-dione.